Severe Sepsis in Older Adults. Issue 3 (July 2015) - Umberger, Reba; Callen, Bonnie; Brown, Mary Lynn
Abstract : Severe sepsis may be underrecognized in older adults. Therefore, the purpose of this article is to review special considerations related to early detection of severe sepsis in older adults. Normal organ changes attributed to aging may delay early detection of sepsis at the time when interventions have the greatest potential to improve patient outcomes. Systems are reviewed for changes. For example, the cardiovascular system may have a limited or absent compensatory response to inflammation after an infectious insult, and the febrile response and recruitment of white blood cells may be blunted because of immunosenescence in aging. Three of the 4 hallmark responses (temperature, heart rate, and white blood cell count) to systemic inflammation may be diminished in older adults as compared with younger adults. It is important to consider that older adults may not always manifest the typical systemic inflammatory response syndrome. Atypical signs such as confusion, decreased appetite, and unsteady gait may occur before sepsis related organ failure. Systemic inflammatory response syndrome criteria and a comparison of organ failure criteria were reviewed. Mortality rates in sepsis and severe sepsis remain high and are often complicated by multiple organ failures. As the numbers of older adults increase, early identification and prompt treatment is crucial in improving patient outcomes.